Precision-Exercise-Prescription in patients with lung cancer undergoing surgery: rationale and design of the PEP study trial. Issue 12 (16th December 2018) - Ulrich, Cornelia M; Himbert, Caroline; Boucher, Kenneth; Wetter, David W; Hess, Rachel; Kim, Jaewhan; Lundberg, Kelly; Ligibel, Jennifer A; Barnes, Christopher A; Rushton, Bailee; Marcus, Robin; Finlayson, Samuel R G; et al.
Abstract : Introduction: Lung cancer is a significant burden on societies worldwide, and the most common cause of death in patients with cancer overall. Exercise intervention studies in patients with lung cancer have consistently shown benefits with respect to physical and emotional functioning. However, to date, exercise training has not been consistently implemented into clinical practice given that interventions have been costly and not aligned with clinical care. Methods/design: The Precision-Exercise-Prescription (PEP) study is a prospective randomised controlled trial comparing the effectiveness and feasibility of a personalised intervention exercise programme among patients with lung cancer undergoing surgery. Two-hundred patients who are diagnosed with stage primary or secondary lung cancer and are eligible to undergo surgical treatment at Huntsman Cancer Institute comprise the target population. Patients are randomised to either the (1) outpatient precision-exercise intervention group or (2) delayed intervention group. The intervention approach uses Motivation and Problem Solving, a hybrid behavioural treatment based on motivational interviewing and practical problem solving. The dosage of the exercise intervention is personalised based on the individual's Activity Measure for Post-Acute-Care outpatient basic mobility score, and incorporates four exercise modes: mobility, callisthenics, aerobic and resistance. Exercise is implemented by physical therapists at study visits from presurgery until 6 months postsurgery. The primary endpoint is the level of physical function assessed by 6 min walk distance at 2 months postsurgery. Secondary outcomes include patient-reported outcomes (eg, quality of life, fatigue and self-efficacy) and other clinical outcomes, including length of stay, complications, readmission, pulmonary function and treatment-related costs up to 6 months postsurgery. Ethics/dissemination: The PEP study will test the clinical effectiveness and feasibility of a personalised exercise intervention in patients with lung cancer undergoing surgery. Outcomes of this clinical trial will be presented at national and international conferences and symposia and will be published in international, peer-reviewed journals. Ethics approval was obtained at the University of Utah (IRB 00104671). Trial registration number: NCT03306992 .